Shiprider model : an analysis of the U.S. proposed agreement concerning maritime counter-drug operations in its legal context - Brown, Kathy-Ann (U.W.I. Faculty of Law Cave HillBB, 1997)
Assesses the legal merits of the Shiprider Agreement. Looks at the nature and scope of the agreement; authorized US counter-drug operations and further contemplated actions; and the privileges and immunities of the US government and its forces. Focuses on some of the more troubling legal aspects of the agreement. Compares the Regional Security System with the Shiprider Agreement.